E-governance and Public Service Delivery in Nepal - Shahi, Binod Kumar (Samsad Journal संसद जर्नल, 2026)
E-governance has emerged as a critical catalyst for transforming public service delivery in Nepal. This study examines the role of E-governance in public service delivery. This review also explores the implementation and impact of ICT-driven e government frameworks, focusing on their role in transforming public service delivery. This article identifies the status, opportunities, constraints and challenges of adopting e-governance with an emphasis on improving public service delivery. Ultimately, effective e-governance has the potential to strengthen institutional capacity, increase transparency, reduce bureaucratic bottlenecks and foster more inclusive, citizen centered governance in Nepal. The finding underscore that the government should focus on making coordinated strategies that combine technological investment with governance reform and capacity building.